Influência da disbiose intestinal induzida pela amoxilina no ciclo estral murino - SILVA, Evandro Neves (2019)
Intestinal dysbiosis refers to the imbalance of the gut microbiota when a specific microorganism population exacerbates or diminishes its proliferation being triggered by several factors, including the use of antibiotics, as amoxicillin, a semisynthetic penicillin of moderate spectrum. Since intestinal dysbiosis is associated with a great variety of immunopathological and reproductive conditions, the main goal of this study was to evaluate the intestinal dysbiosis caused by amoxicillin and its influence on the estrous cycle of mice. For this, female mice isogenic strain of 129Sv/Ev were treated with 500mg/Kg amoxicillin trihydrate or tamponade phosphate (PBS) by gavage for 15 days. Feces of the treated animals were collected for fecal bacterial microbiota population by metagenomics analysis. The amoxicillin-treated animals showed different phyla and bacterial groups in their feces microbiota when compared to the PBS-treated group, showing higher Proteobacteria proliferation and lower presence of Bacteroidetes, demonstrating that the use of amoxicillin induces intestinal dysbiosis. Dysbiotic mice gained body weight when compared to the PBS control group, and both groups did not show any deaths during the treatments. During the treatments, the vaginal cytology was performed by light microscopy, with cells characterization done by flow cytometry and physical evaluation of vaginal parameters performed to determine the estrous cycle phase. These analyses showed that the intestinal dysbiosis caused by the use of amoxicillin not only altered the estrous cycle but also decreased the number of cells present in the cycle phases. In addition, to characterize the possible parameters involved in altering the estrous cycle, caecum and ovarian samples were collected to analyze pro- or anti-inflammatory cytokines IL-1β and IL-10 encoding genes by real-time PCR. The IL-1β expression showed up-regulated in both caecum and ovary from dysbiotic animals when compared to control animals. On the other hand, IL-10 showed down-regulated on the in at dysbiotic group samples when compared to the control group. In conclusion, the results indicated that the use of amoxicillin induces intestinal bacterial dysbiosis influencing the murine estrous cycle and a pro-inflammatory pattern in caecum and ovaries of mice under that antibiotic treatment.